Student Teachers’ Training Needs for Using The Google Forms as Electronic Tests Media from Their Viewpoint (A Field Study on A Sample of Fourth Year Students in The Faculty of Education at Tishreen University) - احمد مطيعة; د. ريم عيسى (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The research aims to determine the training needs of a sample of student teachers in the Faculty of Education at Tishreen University for using the Google Forms as electronic tests media from their viewpoint, and to define its relationship to the two variables: acquisition of a supportive device to access Google forms, and working the father and/or mother in the teaching profession. To achieve the objectives of the research, the descriptive approach was used, and a training needs questionnaire was prepared and distributed to a simple random sample consisting of (225) students in the fourth year, then the data were collected and analyzed statistically, and the two researchers reached the following results: - Student Teachers’ training needs for using the Google Forms as electronic tests media are generally high. - Student Teachers’ acquisition of a supportive device to access the Google Forms does not affect the degree of training needs for using Google Forms as electronic tests media. - Student Teachers’ training needs for using the Google Forms as electronic tests media are reduced for the student teacher whose one parents, at least, works in the teaching profession. The research ended with a set of recommendations, such as paying attention to providing the necessary infrastructure to benefit from the technology of web-based electronic tests in the computer laboratory of the Faculty of Education, and integrating the foundations and skills using the Google Forms as electronic tests media in the vocabulary of practical computer courses for student teachers, and benefiting from the list of training needs in building the training program. Keywords: Training Needs, Google Forms, Electronic Tests.